Redox status of the testes and sperm of rats following exposure to 2,5-hexanedione (2016)
Objectives: Exposure to 2, 5-hexanedione (2, 5-HD) is well known to be associated with reproductive dysfunctions in both humans and animals. However, the role of oxidative stress in 2, 5-HD-induced toxicity in testes and sperm has not yet been studied. Methodology: The present study investigated the influence of 2, 5-HD on antioxidant systems in the testes and epididymal sperm of rats following exposure to 0, 0.25, 0.5, and 1% 2, 5-HD in drinking water for 21 consecutive days. Results: Administration of 0.5% 2, 5-HD significantly (P < 0.05) decreased epididymis weight, whereas 1% 2, 5-HD-treated rats showed significantly decreased body weight, testis, and epididymis weights compared with the control group. Exposure to 2, 5-HD caused a significant dose-dependent increase in the activities of superoxide dismutase, catalase, and glutathione peroxidase in both testes and sperm compared with the control group. Moreover, 2, 5-HD-exposed rats showed significant decrease in glutathione-S-transferase activity and glutathione level with concomitant significant elevation in the levels of hydrogen peroxide and malondialdehyde in both testes and sperm. Testicular and epididymal atrophy with significant, dose-dependent, decrease in epididymal sperm number, sperm motility, and viability were observed in 2, 5-HD-treated rats. Conclusion: 2,5-HD exposure impaired testicular function and sperm characteristics by disruption of the antioxidant systems and consequently, increased oxidative stress in the treated rats.